Negative effects of submandibular botulinum neurotoxin A injections on oral motor function in children with drooling due to central nervous system disorders. (30th November 2016) - van Hulst, Karen; Kouwenberg, Carlyn V; Jongerius, Pieter H; Feuth, Ton; van den Hoogen, Franciscus J A; Geurts, Alexander C H; Erasmus, Corrie E
Abstract : Aim: The aims of this study were: (1) to determine the incidence and nature of adverse effects on oral motor function after first injections of botulinum neurotoxin A (BoNT‐A) in submandibular glands for excessive drooling in children with central nervous system disorders; and (2) to identify independent predictors of these adverse effects. Method: A cohort study involved 209 children (123 males, 86 females, aged 4–27y, median 8y 4mo), who received submandibular BoNT‐A injections for drooling. Adverse effects were categorized into swallowing, eating, drinking, articulation, and other problems. Univariable logistic regression was used to study differences in patients with and without adverse effects. Possible predictors were identified using multivariable logistic regression. Results: Transient adverse effects occurred in 33% of the 209 BoNT‐A treatments. Almost 80% of these were mild, versus 8.7% severe. Approximately 54% of the adverse effects spontaneously resolved within 4 weeks; 3% still existed after 32 weeks. A diagnosis of cerebral palsy, higher range of BoNT‐A dosage, and a pre‐treatment drooling quotient <18% were found to be independent predictors of adverse effects. Interpretation: Before using submandibular BoNT‐A injections for drooling, potential adverse effects should be discussed. Oral motor function needs to be monitored, because existing dysphagia may be worsened. The identified clinical predictors could be helpful to optimize patient selection. What this paper adds: Transient adverse effects of submandibular botulinum neurotoxin A (BoNT‐A) injections on oral motor function occur in 33% of all cases. Predictors of the occurrence of adverse effects of BoNT‐A treatment are diagnosis of cerebral palsy, higher dosage of BoNT‐A, and a pre‐treatment drooling quotient <18%. Although BoNT is a valuable treatment for drooling, careful evaluation before treatment and aftercare are crucial. This article is commented on by Reddihough on pages460–461 of this issue.